2021
DOI: 10.1021/acsomega.0c05077
|View full text |Cite
|
Sign up to set email alerts
|

Combined Colorimetric and Electrochemical Measurement Paper-Based Device for Chemometric Proof-of-Concept Analysis of Cocaine Samples

Abstract: Cocaine (COC) is one of the most widely consumed illegal drugs around the world. Street COC is commonly adulterated with pharmaceutical compounds that mimic or intensify the COC's sensory effect. Adulteration is performed to increase the profit of criminal organizations and each one has their own way of doing it. Therefore, determining the composition of seized COC samples (chemical profile) provides evidence for the police to track criminal organization networks and their activity patterns. Using filter paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
(127 reference statements)
0
14
0
1
Order By: Relevance
“…Detection of these pathogens with conventional methods involves complex, time‐consuming and costly processes that cannot be carried out in the field [60] . Techniques that combine colorimetric paper‐based biosensors [61] with paper‐based electrochemical biosensors [62] have recently become very popular due to their portability, speed, cost, and field availability [63] . Magnetic quantum dots, [64] which may be used instead of fluorescent microspheres in the controlled removal method with synthetic DNAs, which has been used for the first time in this study, not only provide magnet control of captured pathogens, but also provide visual verification.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of these pathogens with conventional methods involves complex, time‐consuming and costly processes that cannot be carried out in the field [60] . Techniques that combine colorimetric paper‐based biosensors [61] with paper‐based electrochemical biosensors [62] have recently become very popular due to their portability, speed, cost, and field availability [63] . Magnetic quantum dots, [64] which may be used instead of fluorescent microspheres in the controlled removal method with synthetic DNAs, which has been used for the first time in this study, not only provide magnet control of captured pathogens, but also provide visual verification.…”
Section: Discussionmentioning
confidence: 99%
“…The dual-mode sensing with colorimetric detection and electrochemical detection using cyclic voltammetry on a μPAD has been demonstrated in several works for environmental and criminal applications. 26,27 Likewise, colorimetric and electrochemical detection can be accompanied each other to allow highly sensitive analysis of various ions that cannot be detected by a color change for clinical applications to extend the working range for ion of interest. In a recent work, potentiometric K + -ISE on transparency polyethylene terephthalate (PET) substrate using in-house stencil printing method and paper-based device was combined.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS) has been used to detect a variety of molecules [ 6 , 7 , 8 , 9 , 10 ] because SERS-based methods only need a small sample and take a few seconds to achieve the multiplexed detection of molecules with high sensitivity. Many studies have reported the SERS detection of drugs, including cannabinoid [ 11 ], cocaine [ 12 , 13 , 14 , 15 , 16 , 17 ], flunitrazepam [ 18 ], alpha-methyltryptamine [ 19 ], heroin [ 17 , 20 ], ketamine [ 21 ], morphine [ 13 , 22 ], benzodiazepine [ 23 ], methamphetamine [ 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], amphetamine [ 31 ], opioid [ 32 ], 3,4-methylenedioxymethamphetamine (MDMA) [ 25 , 27 , 28 , 33 ], 4-MMC [ 34 , 35 ], MC [ 25 ], barbiturate [ 36 ], and sulfa drugs [ 37 ]. While the plasmonic properties of nanostructured substrates or nanoparticles used for SERS measurements is critical for the sensitive detection of molecules, it has been demonstrated that sample pretreatment is also very important for the SERS detection of drugs in biological samples such as urine [ 14 , 25 , 27 ,…”
Section: Introductionmentioning
confidence: 99%